Taxonomic studies on Agapetes in Myanmar I: Agapetes reflexiloba, a new species from Kachin State, and notes on three rediscovered species including two new records for Myanmar - Yang, Bin; Ding, Hong-Bo; Zhou, Shi-Shun; Maw, Mya Bhone; Maung, Kyaw Win; Tan, Yun-Hong (Phytotaxa, 2019)
A new species of Ericaceae, Agapetes reflexiloba, from Putao, Kachin State, Myanmar, is described and a colour plate is provided, affiliated to Agapetes sect. Agapetes ser. Graciles Airy-Shaw. The new species is morphologically similar to A. nutans, A. linearifolia and A. angustifolia of the Series Graciles in having linear to lanceolate narrow leaves and corymbose-racemose inflorescences and very short filaments. It is, however, readily distinguished from its three relatives by having a purplish red to dark red acuminate corolla apex in flower buds and conspicuously reflexed corolla lobes in anthesis, and corolla light brownish yellow to brownish yellow, and with 5 deep purple red zig-zag stripes. The rediscovery of Agapetes bhareliana and A. linearifolia is also reported from Kachin state, Northern Myanmar, after a gap of more than eight decades. Both are new records for Myanmar. Agapetes nana was also recollected 64 years after the collection made by F. Kingdon Ward between 1952 and 1953. Agapetes nana (Griff.) Hook. f. var. robusta Airy Shaw is newly proposed as a synonym of A. nana. A revised taxonomic description along with colour plate and distributional map are provided.